Effect of temperature and humidity on the adhesion strength and damage mechanism of shotcrete-surrounded rock. (15th October 2016) - Tang, Yang; Xu, Guobin; Lian, Jijian; Su, Hui; Qu, Chunlai
Highlights: Adhesion strength at the shotcrete–rock contact in a geothermal and humid environment was got. CT scanning technology was used to evaluate shotcrete-surrounded rock internal defects. The mechanism of adhesion strength under the effects of temperature, relative humidity and curing time was analysed. Abstract: A novel test control system is used to assess the effects of temperature and humidity on the adhesion strength of shotcrete-surrounded rock. Analysis of the internal structure and defect volume reveals that the adhesion strength increases with relative humidity (RH), whereas higher temperatures and longer setting times increase the risk of shotcrete dehydration through an increase in porosity. The critical temperature at which adhesion strength is lost also increases with RH. This shows that temperature, RH and setting time all greatly influence the adhesion strength of shotcrete-surrounded rock, which is of relevance to diversion tunnel construction in highly geothermal environments.